The mammalian neocortex new pyramidal neuron: a new conception - Marín-Padilla, Miguel (Frontiers in Neuroanatomy, 2014)
Mammals’ new cerebral cortex (neocortex) and the new type of pyramidal neuron are mammalian innovations that have evolved for operating their increasing motor capabilities using essentially analogous anatomical and neural makeups. The human neocortex starts to develop in the 6-week-old embryo with the establishment of a primordial cortical organization that resembles the primitive cortices of amphibian and reptiles that operated his early motor activities. From the 8th to the 15th week of age, the new pyramidal neurons, of ependymal origin, are progressively incorporated within this primordial cortex forming a cellular plate that divide its components into those above it (neocortex first lamina) and those below it (neocortex subplate elements). From the 16th week of age to birth and postnatally, the new pyramidal neurons continue to elongate functionally their apical dendrite by adding synaptic membrane to incorporate the needed sensory information for operating the animal muscular activities. The new pyramidal neuron’ distinguishing feature is the capacity of elongating anatomically and functionally its apical dendrite (its main receptive surface) without losing its original attachment to first lamina or the location of its soma retaining its essential nature. The number of pyramidal cell functional strata established in the motor cortex increases and reflects each mammalian species motor capabilities: the hedgehog needs 2 pyramidal cell functional strata to carry out all its motor activities, the mouse three, cat four, primates 5 and humans 6. The presence of six pyramidal cell functional strata distinguish the human motor cortex from that of others primates. Homo sapiens represent a new evolutionary stage that have transformed his primate brain for operating his unique motor capabilities, such as speaking, writing, painting, sculpturing including thinking as a premotor activity.